MENGHIDUPKAN KEMBALI IKON WISATA DI DESA WATU RAKA, KABUPATEN ENDE : PENDEKATAN KREATIF DAN INOVASI UNTUK PARIWISATA BERKELANJUTAN - Se, Hyronimus (Tinta Nusantara 2018 Vol.1, 2024)
This research focuses on the development of community-based tourism (community based tourism) as an effort to encourage sustainable tourism development. The increase in tourism destinations and investment which makes the tourism sector a key factor in income, job creation and business development is the background of this research. Therefore, an approach is needed that contains the concept of sustainable tourism development that involves the active participation of local communities. The concept of sustainable tourism has four main principles which consist of, being environmentally sustainable, socially and culturally acceptable, economically viable and making appropriate use of existing technology. This concept is one of the strategies in community-based tourism to achieve the goals of sustainable tourism development by involving the community in its management. Previous research shows that local community-based tourism development is able to provide positive impacts such as improvements in the economic sector, development of an entrepreneurial spirit and increased community creativity. There are three principles in the community-based tourism development strategy, namely: 1) Involving the community in every decision making, 2) There is certainty from local communities to receive benefits from tourism activities, 3) Providing training and educationtourism for local communities. Apart from that (community bass tourism) can be identified as a strategy for community economic development through empowerment, independence, conservation, sustainability and cultural improvement for more optimal livelihoods in the community